JAMAICA : harnessing the winds of change. (1993)
Examines some of the key issues facing Jamaica, and looks at the efforts which are being made to tackle them. Notes that government is faced with the challenge of fostering an enterprise while maintaining social equilibrium, whereas the private sector must grasp the new opportunities which have been presented to it.
DC